An intra-individual analysis of players' perceived coaching behaviours, psychological needs, and achievement goals - Wang, C. K. J.; Koh, K. T.; Chatzisarantis, N. (International Journal of Sports Science and Coaching, 2009)
In Original Research, John Wang, Koh Koon Teck and Nikos Chatzisarantis examine the relations between perceptions of coaching behaviours, psychological needs, achievement goals and motivational indicators (enjoyment and effort) at an intra-individual level in a study of 264 high-school basketball players aged 14-17 years from 19 schools in Singapore. Cluster analysis from a battery of questionnaires found three distinct groups that differed significantly in terms of intrinsic motivation, perceived needs satisfaction, and achievement goals. The results of this study, in conjunction with previous research, point to a motivational sequence proposed by Mageau and Vallerand, which includes the needs of autonomy, competence and relatedness from Deci and Ryan`s Self Determination theory: Perceived coaching behaviours and the goals structure set up by the coach influence athletes` behavioural regulations through the fulfilment of the three psychological needs. The more the athlete perceives the three needs are being satisfied, the more self-determined one`s behaviour will be. The resulting consequences will be more motivational adaptive behaviours, such as seeking challenge, persistence during failure and feelings of pride and accomplishment.